Mesenchymal Stem Cell-Based Therapy of Inflammatory Lung Diseases: Current Understanding and Future Perspectives - C. Randall Harrell; Ruxana Sadikot; Jose Pascual; Crissy Fellabaum; Marina Gazdic Jankovic; Nemanja Jovicic; Valentin Djonov; Nebojsa Arsenijevic; Vladislav Volarevic (Stem Cells International)
During acute or chronic lung injury, inappropriate immune response and/or aberrant repair process causes irreversible damage in lung tissue and most usually results in the development of fibrosis followed by decline in lung function. Inhaled corticosteroids and other anti-inflammatory drugs are very effective in patients with inflammatory lung disorders, but their long-term use is associated with severe side effects. Accordingly, new therapeutic agents that will attenuate ongoing inflammation and, at the same time, promote regeneration of injured alveolar epithelial cells are urgently needed. Mesenchymal stem cells (MSCs) are able to modulate proliferation, activation, and effector function of all immune cells that play an important role in the pathogenesis of acute and chronic inflammatory lung diseases. In addition to the suppression of lung-infiltrated immune cells, MSCs have potential to differentiate into alveolar epithelial cells in vitro and, accordingly, represent new players in cell-based therapy of inflammatory lung disorders. In this review article, we described molecular mechanisms involved in MSC-based therapy of acute and chronic pulmonary diseases and emphasized current knowledge and future perspectives related to the therapeutic application of MSCs in patients suffering from acute respiratory distress syndrome, pneumonia, asthma, chronic obstructive pulmonary diseases, and idiopathic pulmonary fibrosis.